An efficient approach to the modeling of compressive transverse cracking in composite laminates. (15th September 2015) - Steenstra, W.; van der Meer, F.P.; Sluys, L.J.
Abstract: A wedge-shaped failure mechanism occurs when a composite ply in a laminate is loaded under transverse compression. Therefore failure models developed for tension are not straightforwardly applicable to compression. For models that represent matrix cracks as discontinuities, the inclined crack topology complicates algorithms considerably. In this paper, a method is introduced to approximate the behavior of inclined cracks while avoiding these complications. Rather than adapting the crack topology, a transformation is applied in the evaluation of the cohesive law. The method is applied on predefined interface elements in a 2D model, as well as on cohesive segments in the extended finite element method in a 3D model. It is found that the compressive failure of composite laminates including the wedge effect can be approximated accurately with this method using a vertical crack plane. In 3D, a variable fracture plane angle is taken into account with the method, which means that the whole range of failure modes, from tensile through shear-dominated to compressive failure can be covered in a single approach.